Combination of conditional cash transfer program and environmental health interventions reduces child mortality: an ecological study of Brazilian municipalities - Anelise Andrade de Souza; Sueli Aparecida Mingoti; Rômulo Paes-Sousa; Leo Heller (BMC, 2021)
Abstract Background This study aims to assess the interactive effects of Brazilian public interventions, environmental health programs (access to water, sanitation and solid waste collection) and a Conditional Cash Transfer Program (PBF), on the mortality reduction due to diarrhea and malnutrition among children under 5 years old. Methods The study design is ecological, with longitudinal analysis in a balanced panel. The period covered is 2006 to 2016, including 3467 municipalities from all regions of the country, which resulted in 38,137 observations. The generalized linear models were adjusted considering the Negative Binomial (NB) distribution for the number of deaths due to malnutrition and diarrhea, with fixed effects. NB models with and without zero-inflation were assessed. Subsequent interaction models were applied to assess the combined effects of the two public policies. Results In relation to the decline of mortality rates due to diarrhea in the municipalities, positive effect modification were observed in the presence of: high coverage of the target population by the PBF and access to water, 0.54 (0.28-1.04) / 0.55 (0.29-1.04); high coverage by the total population by the PBF and access to water, 0.97 (0.95-1.00) and high coverage by the total population by the PBF and access to sanitation, 0.98 (0.97-1.00). Decline on diarrhea mortality was also observed in the joint presence of high coverage of solid waste collection and access to water, categories 1 (> 60% ≤85%): 0.98 (0.96-1.00), 0.98 (0.97-1, 00) and 2 (> 85% ≤ 100%): 0.97 (0.95-0.98), 0.97 (0.95-0.99). Negative effect modification were observed for mortality due to malnutrition in the presence of simultaneous high coverage of the total population by the PBF and access to sanitation categories 1 (≥ 20 < 50%): 1.0061 (0.9991-1.0132) and 2 (≥ 50 < 100%): 1.0073 (1.0002-1.0145) and high coverage of the total population by the PBF and solid waste collection, 1.0004 (1.0002-1.0005), resulting in malnutrition mortality rates increase. Conclusion Implementation of environmental health services and the coverage expansion by the PBF may enhance the prevention of early deaths in children under 5 years old due to diarrhea, a poverty related disease.